Occupation: Journalist – Young, female and without fixed employment? - Prandner, Dimitri; Lettner, Martina (Momentum Quarterly, 2012)
Change is one of the constants in the media sector for more than four decades now. And while the structural transformations within the field of mass media and journalism have already been basis of academic research, the situation and inequality that young female journalists are confronted with in Austria has not been described yet. Based on empirical research done by the University of Salzburg in 2010 (Hummel et al. 2010) and employing the theory of the French sociologist Pierre Bourdieu this article seeks to display both, the structurally existing and the perceived inequality experienced by female journalists, their reasons, and possible answers to these issues.
Keywords: Journalism; Austria; Inequality; Bourdieu